Complex class 1 integrons harboring CTX-M-2-encoding genes in clinical Enterobacteriaceae from a hospital in Brazil - Dropa, Milena; Balsalobre, Livia Carminato; Lincopan, Nilton; Matté, Glavur Rogério; Matté, Maria Helena (The Journal of Infection in Developing Countries, 2015)
Introduction: CTX-M enzymes are the most prevalent extended-spectrum beta-lactamases (ESBLs) in Brazil and around the world. The spread of CTX-M lies in their ability to be mobilized by insertion sequences and integrons. This study aimed to identify the mobile genetic structures associated with blaCTX-M genes from clinical Enterobacteriaceae strains. Methodology: Twenty-eight clinical non-clonal Enterobacteriaceae were screened by PCR for the presence of blaCTX-M genes and class 1 integrase (int1), and for the association of blaCTX-M with class 1 integrons. Plasmid incompatibility groups were assessed by PBRT. Wild-type plasmids were transformed into electrocompetent E. coli, and the S1-PFGE technique was used to verify the presence of high-molecular-weight plasmids in both wild-type strains and E. coli transformants. Results: Sequencing showed that strains carried blaCTX-M-2 (n = 25) and blaCTX-M-59 (n = 3) genes inserted into the 3’-end of complex class 1 integrons. Thirteen strains also carried blaTEM and blaSHV genes. CTX-M-2/59-containing complex class 1 integrons were also present in E. coli transformants. The most frequent Inc groups were IncA/C (n = 10) and IncF (n = 8). Heavy plasmids were observed in both wild-type strains and E. coli transformants. Conclusions: The presence of the same blaCTX-M-2-group-containing genetic structure in seven Enterobacteriaceae species isolated at seven hospital wards shows the great mobility potential of complex class 1 integrons. Also, this is the first report of TEM-15, SHV-45, and SHV-55 in Latin America. The genetic environment of blaCTX-M-2 accounts for their maintenance and spread among Gram-negative bacteria.